The effect of electromagnetic radiation due to mobile phone use on thyroid function in medical students studying in a medical college in South India - Nikita Mary Baby; George Koshy; Anna Mathew (Indian Journal of Endocrinology and Metabolism, 2017)
Background: Enormous increase in mobile phone use throughout the world raises widespread concerns about its possible detrimental effect on human health. Radiofrequency waves are emitted by cell phones. They are non-ionising and the effect on the thyroid gland is part of their non thermal effects. The thyroid gland may be particularly vulnerable to this effect because of its normal anatomical position. Materials and Methods: The study was done to explore the association between radiation exposure and thyroid dysfunction among mobile phone users. It had an exploratory design and unit survey method to collect information from all medical students in a medical college in South India. Inclusion criteria included active use of mobile phone prior to and during the study period. Criteria for exclusion was presence of pre-existsting thyroid disease,thyroid nodule,thyroid goitre/nodule and altered thyroid function. Results: The sample size was 83 undergraduate students. 71% of respondents had no family history of thyroid illness. Among the remainder,20.5% had a first degree relative with thyroid dysfunction,8.4% had a second degree relative affected. Clinical examination revealed that 79.5% of the respondents were normal,13.6% had thyroid swelling,3.6% had symptoms of thyroid dysfunction and 3.6% had both thyroid swelling and symptoms of thyroid dysfunction. 53% of the respondents spent 0.5 hrs on an average talking on the phone daily,28.9% spent 1.5 hrs daily and 10.8% of respondents spent over 3.5 hours. We found there was a significant correlation between total radiation exposure and an increase in TSH among both groups –in those with and without family history of thyroid illness. Conclusion: In our study there was a significant correlation between total radiation exposure and increasing TSH values among both all respondents.